Dweller satisfaction regarding planning requirement and workmanship in low cost housing at Kuantan district / Mohd Syukri Mat Ghani. - Mat Ghani, Mohd Syukri (2010)
Dweller satisfaction is a most important element in housing industry. To achieve the satisfaction especially for low cost housing dweller, government has implemented various guideline to ensure construction of low cost housing is uniform and comply with standard. A part of the guideline that provided is planning and design guideline, construction industry standard (CIS) 1 and 2, and latest is Quality Assessment System in Construction (QLASSIC) based on Construction Industry Standard (CIS) 7. The objective of the study is to determine dweller satisfaction regarding planning requirement and workmanship in low cost houses in Kuantan District. The data was collected by literature review, checklist, observation and interview on the low cost housing units. The respondent for the study covered seventy five (75) low cost housing dweller in five (5) low cost housing in Kuantan District area. The analysis shows the result that the provisions through government's guideline not fully implemented in the five (5) low cost housings surveyed, because some of the low cost housing area don't have a completed facility and differential design. Besides, there are common workmanship defects experienced by the low cost housing dwellers mostly related to the building construction such as installation aspect, fixing etc. However, most of the dweller still satisfied and gratefully on their houses.